Vitamin E and reduced glutathione in Prochilodus lineatus (curimba) semen cryopreservation (Characiformes: Prochilodontidae) - Daniella A. J. Paula; Estefânia S. Andrade; Luis D. S. Murgas; Viviane O. Felizardo; Elissandra U. Winkaler; Walmes Zeviani; Rilke T. F. Freitas (Neotropical Ichthyology, 2012)
This study investigated the addition of antioxidants vitamin E and reduced glutathione on curimba (Prochilodus lineatus) semen cryopreservation and compared sodium bicarbonate solution and distilled water as activators. The experiment was conducted at the environmental station of CEMIG, in Itutinga-MG, Brazil, between December/2009 and January/2010. Semen samples (n = 7) with semen motility above 80% were diluted in cryoprotectant solutions composed of 10% methanol, 15% lactose and containing different concentrations of antioxidants: 50 (VE50), 100 (VE100) and 250 (VE250) µM of vitamin E, and 0.5 (RG0.5), 1.0 (RG1.0) and 1.5 (RG1.5) mM of reduced glutathione. A solution without antioxidants was used as a control. The semen was diluted at a ratio of 1:4 (100 ìL semen:400 ∝L cryoprotectant solution). The toxicity of the solutions was evaluated by investigating semen motility after 10 min in the solution. The rest of the diluted semen was placed into 0.5 mL straws maintained in nitrogen vapour for 24 hours and packed into a nitrogen liquid cylinder for four days. The samples were thawed in a water bath at 60°C for 8 s and the rate (%) and duration (s) of semen activation with distilled water or sodium bicarbonate was evaluated. In the toxicity test, we found that vitamin E and reduced glutathione were not toxic to curimba semen at any of the tested concentrations (P>0.05). The duration of motility was longer (P<0.05) in semen activated with sodium bicarbonate 1% (163 ± 11 s), which was considered the best activator for semen under these conditions. No significant differences were found between the cryoprotectant solutions used after freezing (P>0.05). Thus, the antioxidants vitamin E and reduced glutathione did not improve the quality of cryopreserved curimba semen, but they did not cause toxic effects to the semen in natura and they did not decrease its quality during cryopreservation. Este estudo avaliou a adição de antioxidantes vitamina E e glutationa reduzida no sêmen criopreservado de curimba (Prochilodus lineatus) e comparou solução de bicarbonato de sódio e água destilada como ativadores. O experimento foi conduzido na estação ambiental da CEMIG, em Itutinga-MG, entre Dezembro/2009 e Janeiro/2010. Sêmen de sete animais, com motilidade espermática acima de 80%, foi diluído em soluções crioprotetoras compostas por metanol 10% e lactose 15% em diferentes concentrações de antioxidantes: 50 (VE50), 100 (VE100) e 250 (VE250) µM de vitamina E, 0,5 (RG5.5), 1,0 (RG1.0) e 1,5 (RG1.5) mM glutationa reduzida e uma solução controle sem antioxidante. O sêmen foi diluído na proporção de 1:4 (100 µL de sêmen: 400 µL de solução crioprotetora). A toxicidade das soluções foi avaliada pela motilidade espermática após de 10 minutos em solução. O restante do sêmen diluído foi armazenado em palhetas de 0,5 mL mantidos em vapor de nitrogênio por 24 horas e estocado em cilindro de nitrogênio líquido por quatro dias. As amostras foram descongeladas em banho-maria a 60°C por 8 segundos e avaliada a taxa (%) e duração (s) pela ativação do sêmen com água destilada e bicarbonato de sódio a 1%. No teste de toxicidade, observamos que os antioxidantes da vitamina E e glutationa, nas diferentes concentrações, não foram tóxicos para o sêmen do curimba (P>0,05). A duração da motilidade foi maior (P<0,05) no sêmen ativado com bicarbonato de sódio, sendo o melhor ativador para o sêmen nestas condições. Não houve diferenças significativas entre as soluções crioprotetoras utilizadas para sêmen antes e após congelamento (P>0,05). Assim, os antioxidantes vitamina E e glutationa reduzida não melhoram a qualidade do sêmen criopreservado de curimba, mas não causam efeitos tóxicos para o sêmen in natura e criopreservados por não diminuir sua qualidade durante a criopreservação.